2002
DOI: 10.1016/s0092-8674(02)01014-0
|View full text |Cite
|
Sign up to set email alerts
|

The β-Catenin/TCF-4 Complex Imposes a Crypt Progenitor Phenotype on Colorectal Cancer Cells

Abstract: The transactivation of TCF target genes induced by Wnt pathway mutations constitutes the primary transforming event in colorectal cancer (CRC). We show that disruption of beta-catenin/TCF-4 activity in CRC cells induces a rapid G1 arrest and blocks a genetic program that is physiologically active in the proliferative compartment of colon crypts. Coincidently, an intestinal differentiation program is induced. The TCF-4 target gene c-MYC plays a central role in this switch by direct repression of the p21(CIP1/WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

108
1,528
1
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,866 publications
(1,656 citation statements)
references
References 41 publications
108
1,528
1
12
Order By: Relevance
“…Both mutations have previously been characterized as highly activating. 20 Transcription mediated by FOXO3 or LEF/TCF, which are associated with PI3K/AKT and Wnt/β-catenin signal transduction, respectively, 7,21 was not altered by either mutation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Both mutations have previously been characterized as highly activating. 20 Transcription mediated by FOXO3 or LEF/TCF, which are associated with PI3K/AKT and Wnt/β-catenin signal transduction, respectively, 7,21 was not altered by either mutation.…”
Section: Resultsmentioning
confidence: 92%
“…In line, loss of intestinal Wnt/β-catenin signals by genetic ablation of the transcription factor TCF4 results in loss of the stem cell compartment and ultimately in loss of the intestinal epithelium in the mouse. 7,8 In contrast, activation of β-catenin is sufficient to modulate intestinal cellular hierarchies toward adenomatous stem cell fates. 9 Sessile serrated adenomas (SSAs) constitute a distinct class of premalignant tumors in the intestine, which are characterized by a saw-toothed and tufted tissue morphology, as well as by unique transcriptional, mutational and epigenetic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…b-Catenin is also found to immunoprecipitate with the APC tumour suppressor protein (Su et al, 1993;Hulsken et al, 1994;Shibata et al, 1994), and has been recently identified as an oncogene (Kim et al, 2002;Minamoto et al, 2002;Kielhorn et al, 2003;Schneider et al, 2003). It is also central to cell signalling, as upon dissociation from E-cadherin, it transits to the nucleus to alter transcriptional profiles (Mason et al, 2002;van de Wetering et al, 2002). A reduction in b-catenin expression decreases the stability of the adhesion complex and likely results in impairment in E-cadherin function (Willert and Nusse, 1998;Lowy et al, 2002;Mason et al, 2002).…”
mentioning
confidence: 99%
“…The TCF4 variant [(designated as dominant negative TCF4 (dnTCF4)] binds the regulatory regions in Wnt‐responsive genes. Nevertheless, due to the disruption of the β‐catenin interaction domain (Korinek et al ., 1997; van de Wetering et al ., 2002), it cannot associate with β‐catenin and acts as a nuclear blocker of canonical Wnt signaling. Additionally, a sequence encoding a tandem dimer (td) of red fluorescent protein Tomato flanked (i.e.…”
Section: Introductionmentioning
confidence: 99%